Investigation of luminescent properties inherent to SrTiO₃:Pr³⁺ luminophor with Al impurity - Marchylo, O.M.; Zavyalova, L.V.; Nakanishi, Y.; Kominami, H.; Belyaev, A.E.; Svechnikov, G.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
The red-emitting SrTiO₃:Pr³⁺,Al luminophors that can be used for the white
light emitting diodes (LEDs) were prepared using the sol-gel method. The starting
materials were SrCl₂, Ti (O – i – C₃H₇)₄, Al(NO₃)₃·9H₂O and PrCl₃. The reaction
between them results in a mixture of compounds that transform into single-phase
SrTiO₃:Pr³⁺,Al after annealing in air. Displacement of Ti out of the SrTiO₃ lattice caused
by substitution with Al and formation of individual crystalline TiO₂ phase (rutile) were
observed. PL spectra show the high-intense red peak (λ = 617 nm), the same high-intense
peak with the full width at half maximum (FWHM) 20 nm was found in
cathodoluminescence spectra. The increase of the aluminium concentration from 0 up to
15 mol.% leads to approximately two-fold increase in the luminance. The latter increases
from 180 up to 350 cd/m²
at the anode voltage 10 kV and current density 30 μA/cm²
.